2021
DOI: 10.1136/emermed-2020-209470
|View full text |Cite
|
Sign up to set email alerts
|

Association between triage level and outcomes at Médecins Sans Frontières trauma hospital in Kunduz, Afghanistan, 2015

Abstract: BackgroundFive million people die annually due to injuries; an increasing part is due to armed conflict in low-income and middle-income countries, demanding resolute emergency trauma care. In Afghanistan, a low-income country that has experienced conflict for over 35 years, conflict related trauma is a significant public health problem. To address this, the non-governmental organisation Médecins Sans Frontières (MSF) set up a trauma centre in Kunduz (Kunduz Trauma Centre (KTC)). MSF’s standardised emergency op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The same is true for triage facilities to categorise RTC patients based on the severity of the injury. In a study from Afghanistan, triage levels were found to correlate well with mortality outcomes, for example, none of the patients triaged as green died or was admitted to the ICU, whereas 90% of patients who died were triaged as red 15. The study observed that the majority of the RTCs occurred in metropolitan locations, and most of them occurred during the daytime.…”
Section: Discussion and Recommendationsmentioning
confidence: 83%
See 1 more Smart Citation
“…The same is true for triage facilities to categorise RTC patients based on the severity of the injury. In a study from Afghanistan, triage levels were found to correlate well with mortality outcomes, for example, none of the patients triaged as green died or was admitted to the ICU, whereas 90% of patients who died were triaged as red 15. The study observed that the majority of the RTCs occurred in metropolitan locations, and most of them occurred during the daytime.…”
Section: Discussion and Recommendationsmentioning
confidence: 83%
“…In a study from Afghanistan, triage levels were found to correlate well with mortality outcomes, for example, none of the patients triaged as green died or was admitted to the ICU, whereas 90% of patients who died were triaged as red. 15 The study observed that the majority of the RTCs occurred in metropolitan locations, and most of them occurred during the daytime. This is consistent with another study from Bangladesh, which found that the majority of RTCs occurred in the morning and urban areas.…”
Section: Discussion and Recommendationsmentioning
confidence: 94%